Admitting risks towards circular economy practices and strategies: An empirical test from supply chain perspective. (1st October 2021) - Dulia, Esrat Farhana; Ali, Syed Mithun; Garshasbi, Maryam; Kabir, Golam
Abstract: This article attempts to evaluate risks associated with circular economy (CE) practices and strategies in circular supply chains (CSCs) in response to the research gap related to the risks in CSCs in the current body of knowledge. There is a need for risk classification and examination for increasing the CSC effectiveness in the industry. These kinds of studies in developing countries like Bangladesh are few. To reach the goals of this study, for evaluating the risk factors obtained from a survey-design and feedback from experts, a fuzzy synthetic evaluation (FSE) approach-based model is developed. The findings revealed that "quality degradation of recycled products" and "CE framework risks" are the most critical risk factors and groups in CSC initiatives, respectively. The findings are essential because they enable experts to understand the urgency in managing risks associated with CSC concepts. Therefore, the findings can be used to help industrial managers, government policymakers, and other stakeholders across the CSC of interest to implement and maintain the CSCs given the acknowledged risks.